Credit supply, firms, and earnings inequality - Christian Moser; Farzad Saidi; Benjamin Wirth; Stefanie Wolter (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2021)
We study the distributional consequences of monetary policy-induced credit supply in the labor market. To this end, we construct a novel dataset that links worker employment histories to firm financials and banking relationships in Germany. Firms in relationships with banks that are more exposed to the introduction of negative interest rates in 2014 experience a relative contraction in credit supply, associated with lower average wages and employment. These effects are heterogeneous within and between firms. Within firms, initially lower-paid workers are more likely to leave employment, while initially higher-paid workers see a relative decline in wages. Between firms, wages fall by more at initially higher-paying employers. In this way, credit affects the distribution of pay and employment in line with predictions of an equilibrium model with both credit and search frictions.
Keywords: J31; E24; J23; G21; E51; 330; Wages; Employment; Worker and Firm Heterogeneity; Monetary Policy; Negative Interest Rates